Comparison of Upper Extremity Function in Women With and Women Without a History of Breast Cancer. Issue 3 (7th February 2020) - Fisher, Mary Insana; Capilouto, Gilson; Malone, Terry; Bush, Heather; Uhl, Timothy L
Abstract: Background: Breast cancer treatments often result in upper extremity functional limitations in both the short and long term. Current evidence makes comparisons against a baseline or contralateral limb, but does not consider changes in function associated with aging. Objective: The objective of this study was to compare upper extremity function between women treated for breast cancer more than 12 months in the past and women without cancer. Design: This was an observational cross-sectional study. Methods: Women who were diagnosed with breast cancer and had a mean post–surgical treatment time of 51 months (range = 12–336 months) were compared with women who did not have breast cancer (CTRL group). Self-reported upper extremity function using the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire and shoulder range of motion, strength, and muscular endurance were measured. Participants were divided into 3 groups: breast cancer involving the nondominant limb (BC-ND), breast cancer involving the dominant limb (BC-DOM), and CTRL. Results: A total of 59 women in the CTRL group, 23 women in the BC-ND group, and 28 women in the BC-DOM group completed measures. Mean DASH scores in women with breast cancer were higher than those of women in the CTRL group, regardless of the limb on which cancer occurred (Cohen d  = 1.13; 95% CI = 2.20 to 16.21) Range of motion for the BC-ND group was significantly less for flexion (Cohen d  = 1.19, 95% CI = −13.08 to −0.11) and external rotation (Cohen d  = 1.11, 95% CI = −18.62 to −1.98) compared with the CTRL group. Strength in the BC-ND group was 23% to 25% lower in the CTRL group for external (Cohen's d  = 0.89, 95% CI = 0.09 to 0.12) and internal rotation (Cohen d  = 0.92, 95% CI = 0.10 to 0.13). Endurance was not significantly different in the 3 groups. Limitations: Some participants had rehabilitation, which may have skewed results. The range of post–surgical treatment times was broad, making it difficult to determine when function returned. Muscular endurance measures demonstrated a ceiling effect and large variance, limiting the ability to distinguish differences among participants. These results may not be generalizable to the subset of women who were treated with lumpectomy, sentinel node biopsy, or chest wall radiation alone or who underwent a contralateral prophylactic mastectomy. Conclusion: In the long term, women with breast cancer have lower self-reported shoulder function than women without breast cancer. Motion and strength are lower among women who have experienced cancer on the nondominant limb.